Structural characterization of sports supplement market - Castro Arteta, Alonso (2022)
Sports supplements are vital as nutritional complement and improve people's physical performance. In this sense, the objective of this study was to identify and characterize the variables that determine the sports supplement market and the actors who drive it, based on a study of the Peruvian market. For this purpose, a systematic literature review and a structural analysis of descriptive scope were used with the help of seven experts knowledgeable about the industry and the MICMAC structural characterization software. The results present as key variables of the system the economic development of the nutritional supplements market, the growth of e-commerce type companies, the fitness culture, the use of social networks and technological advances in the food industry. The most influential actors end up being local and international organizations linked to the nutritional market, the sports institutes and training centers. This study constitutes a starting point for the design of future scenarios and the strategic planning of the sports supplements market in Ibero-américa.